2022
DOI: 10.3390/su14159331
|View full text |Cite
|
Sign up to set email alerts
|

Field Applicability of Earthwork Volume Calculations Using Unmanned Aerial Vehicle

Abstract: The earthwork volume must be calculated as accurately as possible for economical construction and cost savings. In particular, when calculating the areas and volumes of irregular curved terrains such as mountains, reservoirs, lakes, and coasts, the vertical assumptions for the boundary equation must be rationally and systematically established. This study focuses on earthwork volume calculation technology using UAV (unmanned aerial vehicle). UAV can be used for various types of work, including checking the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A UAV, commonly known as a drone, is an aircraft that is not guided by any human pilot but autonomously by remote control and carries sensors within them. UAVs are widely distributed in surveying [ 8 ] construction sites to capture 3D images and determine the progress, estimating the volume of earthwork [ 3 , 9 , 10 , 11 ], assessing and inspecting existing structures [ 4 , 12 ] and the environment [ 4 , 13 ]. These UAVs are a type of aerial platform that can acquire digital images and georeferencing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A UAV, commonly known as a drone, is an aircraft that is not guided by any human pilot but autonomously by remote control and carries sensors within them. UAVs are widely distributed in surveying [ 8 ] construction sites to capture 3D images and determine the progress, estimating the volume of earthwork [ 3 , 9 , 10 , 11 ], assessing and inspecting existing structures [ 4 , 12 ] and the environment [ 4 , 13 ]. These UAVs are a type of aerial platform that can acquire digital images and georeferencing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated a wide range of applications of UAVs in civil engineering and construction. Engineering personnel has been applying UAVs in surveying [ 9 ] to determine progress activities [ 10 ], estimate earthwork volume and cut/fill quantities [ 3 , 11 ], stockpile volume estimation, and more related topics. However, most of the available research in construction has focused on the application of UAVs in quantity takeoff.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the reliability of these approaches, some weaknesses exist, such as the high computational burden required to process point clouds or the expertise requested by operators to effectively exploit these tools. This prevents the spreading of the technology in many sectors which could benefit from quick and reliable volume estimates, such as logistics [ 3 ], earthworks [ 4 ], or agriculture [ 5 ].…”
Section: Introductionmentioning
confidence: 99%